Health Based Quality Life and the Financial Burden among the People of India Experiencing Chronic Diseases - Arya Kumar; Farook Sayyad; Raghavan Srinivasan; Somnath Chatterjee; Abhijeet Chavan; Sweta Leena Hota (ACHSM, 2023)
The financial burden influences elderly individuals' health-related quality of life (HRQoL). Very little is understood concerning the association between financial strain and HRQoL in vulnerable groups. This study aimed to examine the relationships among financial load and HRQoL of Odisha who suffer from chronic illness, along with cancer. Techniques: Throughout this cross-sectional investigation, 72 Citizens of Odisha (aged 60-89) with one or maybe more chronic diseases took part in a randomized preliminary trial. We investigated financial burden components using factor analysis. A 27-point FACT-G (Functional Assessment of Cancer Therapy-General) was applied to measure HRQoL. The correlations among financial burden and HRQoL sub-dimension were investigated using multiple linear regression. The factor analysis showed three financial burden constructs: health costs issues, financial burden medication compliance, and monetary stress. The financial burden was related to lower HRQoL throughout various areas in this research of older adults of Odisha with chronic conditions.